Peran Komunikasi Keluarga Dalam Meningkatkan Kesejahteraan Psikologis Remaja Pada Keluarga Broken Home - Wandira, Ayu Febrya; Narti, Sri; Dianthi, Martha Heriniazwi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study aims to determine the role of family communication in improving the psychological well-being of adolescents in broken home families. This research is a qualitative research using the triangulation method, namely observation, documentation and interviews as well as literature studies. This type of research is field research which means that the researcher observes directly to the field to get maximum results. Family communication is analyzed as factors that affect the psychological well-being of adolescents. The results of the study show that the role of family communication has not been applied massively by parents to adolescents affected after the divorce of their parents, giving rise to the term broken home, which is a family in which there is no peace, prosperity and disharmony. Family communication in broken home families shows a bad parental self-image for children because parents do not put themselves like parents to children who need guidance after divorce. So that the psychological atmosphere in children is disturbed such as feeling afraid, depressed and not expressive. In families that are broken home, there is a parental communication style that changes to be more aggressive towards children. This is because the way parents lead their children is not done as they should and parents think too much about their own feelings, so that children feel uncaring and more comfortable outside the home. The language ethics used by parents when talking to children have changed. Parents use word choices and body gestures that make children feel pressured so that children keep their distance from their parents because they think that parents are no longer a safe place.